Values and ethics in school education - Luther, M. M. (New Delhi ; New York : Tata McGraw-Hill Pub. Co., 2001)
With special reference to India.
Machine generated contents note: 1. Modern Society and School Education -- Global Scenario 1 -- The Indian Scenario 5 -- 2. Trends in School Education -- International Trends 25 -- Scenario of School Education in India 55 -- Impact of Information Technology 90 -- 3. School Education in India- -- A Conceptual Framework -- Wisdom, Knowledge and Information 101 -- Indian Heritage-Traditional Values 104 -- Values and Ethics Defined 114 -- Science, Technology and Moral Education 128 -- Education and Religion 133 -- 4. Techniques and Strategies -- General Principles of Imparting -- Human Values in Schools 152 -- Techniques and Methodologies 155 -- Formal and Informal Methods 158 -- Curricula Development 160 -- 5. Activities, Programmes and Value Education -- Mass Activities 166 -- Group Activities 177 -- Individual Activities 192 -- 6. Child Development -- The Home Environment 198 -- * Development Stages: The Psychologist's View 200 -- Pre-school Days 201 -- School Days 203 -- 7. Spiritual Education -- Why Spiritual Education 218 -- Development of Intuition 224 -- Development of Consciousness 226 -- Elements of Spiritual Education 228 -- 8. Yoga, Meditation and Performance -- Yoga Defined 236 -- An Outline of Yogic Education 240 -- Meditation 245 -- Globalising Yoga 258 -- 9. Teacher: The Crucial Factor -- The Principal 262 -- The School Teacher 266 -- Training of Teachers 282 -- 10. Parents and School Education -- Home as Character-building School 291 -- Mother's Influence 292 -- Parents' Paradigms 294 -- Parent-Teacher Cooperation 296 -- 11. Government's Nonchalance -- , Committees and Commissions on Value Education 30; -- , Scheme of Assistance for Strengthening Culture -- and Values in Education 310 -- 12. Pioneering Value Education in Schools: -- Some Case Studies -- The Pace-setters 315 -- Free Progress Concept of Sri Aurobindo -- Education Society 317 -- The Psychic Dimension 323 -- Spiritual Education 323 -- Apeejay Schools 331 -- St Xaviers' Group of Schools 332 -- "Nai Talim" 335 -- Shantiniketan 336 -- .Dayalbagh Educational Institute 338 -- Banasthali Vidyapeeth 339 -- Bharati Vidyapeeth 339 -- Ram Krishna Institute of Moral and Spiritual -- Education, Mysore 340 -- Rishi Valley School 340 -- .Sathya Sai Bal Vikas Programme 341 -- .Jameatul Hidaya, Jaipur 341 -- 13. A Vision of the Future -- * What Next? 344 -- Historical Perspective 349 -- * De-emphasising Some Western Concepts 350 -- Students' Role in Policy Making 353 -- * Revival'f Indian Traditions and -- a New Look Curriculum 355 -- Counselling Students and Parents -- as a Part of the System 362 -- .The New Mllennium Teachers 364 -- * Resolving NonAteaching Problems 368 -- Framing, Updating and Implementation -- of Effective Education Policies 371 -- * A Mission for India 380 -- Annexures -- Glossary -- Bibliography -- Index.
Includes statistical tables.
Includes bibliographical references (pages [432]-433) and index.
BIED
Keywords: Moral education -- India; Education -- Moral and ethical aspects -- India